Juridical Analysis Of The Causes Of The Non- Development Of The People's Shipping Industry In Indonesia Due To The Fleet Aging And Extinction Of The Fleet (Research Study In Batam And Tanjung Pinang) - Topan Wishnu Candra; Soerya Respationo; Parameshwara Parameshwara; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The artisanal shipping industry in Indonesia, particularly in Batam and Tanjungpinang, has experienced significant stagnation and decline due to the aging fleet and fleet extinction. The background of this study is based on the importance of the artisanal shipping industry in supporting the local and national maritime economy, as well as the major challenges facing the sector in maintaining efficient and sustainable operations. The purpose of this research is to analyze the juridical factors that cause the non-development of the people's shipping industry in the area, as well as identify legal measures that can support the development of this industry. The research method applied combines normative and empirical approaches through case studies in Batam and Tanjungpinang. Data was collected through in-depth interviews with boat owners, fishermen, government officials, and maritime law experts, as well as analysis of relevant documents. The research integrates John Austin's positive law theory, Lawrence M. Friedman's legal system theory, and systems theory to analyze interactions within the maritime legal system. The results show that burdensome regulations, lack of access to financing, declining competitiveness, as well as environmental impacts and socio-economic factors are the main causes of the underdevelopment of the community shipping industry. Strict regulations and high operational costs make it difficult for small boat owners to comply with regulations, while limited access to financing hinders fleet rejuvenation and upgrades. An aging and inefficient fleet lowers the industry's competitiveness, and environmental pollution from old vessels worsens operating conditions. Suggestions include revising regulations to simplify and reduce administrative burdens, providing accessible financing and subsidy schemes, improving port infrastructure, and training and certification programs for ship owners and crew. In addition, international cooperation is also needed to adopt technology and best practices in the shipping industry. The implementation of these recommendations is expected to support the development of the small-scale shipping industry in Batam and Tanjungpinang, improve competitiveness, and make a greater contribution to Indonesia's maritime economy.